Play-based interventions for reducing blood pressure among older adults with hypertension: A narrative literature review - Syarifah Ayni Harahap; Yufitriana Amir; Siti Rahmalia Hairani Damanik (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Hypertension is a common health problem among older adults and requires both pharmacological and non-pharmacological management. Play-based activities may provide cognitive, psychological, social, and physical benefits, but their effects on blood pressure remain unclear. Purpose: To summarize evidence on play-based interventions and their potential effects on blood pressure and related health outcomes among older adults. Method: A narrative literature review was conducted using Google Scholar, PubMed, and ScienceDirect. Studies published between 2018 and 2026 were screened using predefined eligibility criteria. Thirteen articles were included and synthesized descriptively. Results: The majority of respondents had adequate knowledge (69%), negative attitudes (56%), and good management (78%). Bivariate testing showed a significant relationship between knowledge and management of primary dysmenorrhea (p = 0.027) and attitudes and management of primary dysmenorrhea (p = 0.000). The review results showed that most studies used pre-experimental and quasi-experimental designs. The types of play therapy found were puzzle games and ball throwing. Of the 13 articles, eight discussed puzzle therapy, with seven demonstrating effective results in improving cognitive function and reducing stress, and two articles demonstrating reduced blood pressure. Meanwhile, five articles discussed ball-throwing therapy, with four articles demonstrating increased physical activity and reduced anxiety, and two articles demonstrating reduced blood pressure. The instruments used included the MMSE, HARS, a sphygmomanometer, and observation sheets. Conclusion: Play-based interventions may support cognitive, psychological, and physical well-being among older adults. However, current evidence is insufficient to confirm their effectiveness in reducing blood pressure, particularly for intergenerational interventions involving preschool children.